Does tax competition really promote growth? - Marko Koethenbuerger; Benjamin Lockwood (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper considers the relationship between tax competition and growth in an endogenous growth model where there are stochastic shocks to productivity, and capital taxes fund a public good which may be for final consumption or an infrastructure input. Absent stochastic shocks, decentralized tax setting (two or more jurisdictions) maximizes the rate of growth, as the constant returns to scale present with endogenous growth implies extreme tax competition. Stochastic shocks imply that households face a portfolio choice problem, which may dampen down tax competition and may raise taxes above the centralized level. Growth can be lower with decentralization. Our results also predict a negative relationship between output volatility and growth, consistent with the empirical evidence.
Keywords: H77; E62; F43; 330; Steuerwettbewerb; Fiskalische Dezentralisierung; Wirtschaftswachstum; Risiko; Neue Wachstumstheorie